Genome-wide association with select biomarker traits in the Framingham Heart Study. - Benjamin, Emelia J.; Dupuis, Josée.; Larson, Martin G.; Lunetta, Kathryn L.; Booth, Sarah L.; Govindaraju, Diddahally R.; Kathiresan, Sekar.; Keaney, John F.; Keyes, Michelle J.; Lin, Jing-Ping.; Meigs, James B.; Robins, Sander J.; Rong, Jian.; Schnabel, Renate.; Vita, Joseph A.; Wang, Thomas J.; Wilson, Peter WF.; Wolf, Philip A.; Vasan, Ramachandran S. (2016)
Background: Systemic biomarkers provide insights into disease pathogenesis, diagnosis, and risk stratification. Many systemic biomarker concentrations are heritable phenotypes. Genome-wide association studies (GWAS) provide mechanisms to investigate the genetic contributions to biomarker variability unconstrained by current knowledge of physiological relations.; Keywords: base pair, chromosome, C-reactive protein, Family Based Association Tests, Generalized Estimating Equations, Genome-wide association studies, linkage disequilibrium, logarithm of the odds (base 10), monocyte chemoattractant protein-1, single nucleotide polymorphisms.; Springer Open.